Reduced antiplatelet effect of aspirin is associated with low-grade inflammation in patients with coronary artery disease - Larsen, Sanne Bøjet; Grove, Erik Lerkevang; Kristensen, Steen Dalby; Hvas, Anne-Mette (Thrombosis and Haemostasis, 2013)
Inflammation has been proposed to modify platelet function. This may lead to increased platelet reactivity and reduced antiplatelet drug efficacy in patients with coronary artery disease (CAD). However, this hypothesis has not been investigated in stable CAD patients receiving aspirin as mono antiplatelet therapy. It was the objective of this study to investigate the association between platelet reactivity, the inflammatory markers high-sensitive C-reactive protein (hs-CRP) and interleukin-6 (IL-6), and platelet activation. We performed a cross-sectional study on 524 stable high-risk CAD patients. Among these, 91% had a history of myocardial infarction, 23% had type 2 diabetes, and 13% had both. All patients received 75 mg aspirin daily as mono antiplatelet therapy. Platelet reactivity was assessed by multiple electrode aggregometry (Multiplate®, MEA) and VerifyNow®. Inflammation was evaluated by hs-CRP and IL-6. Platelet activation was assessed by soluble P-selectin (sP-selectin), and cyclooxygenase-1 inhibition was evaluated by measurement of serum thromboxane B2. Hs-CRP levels were significantly higher in upper platelet reactivity tertile patients than in lower platelet reactivity tertile patients (p≤0.02). Similar results were obtained with IL-6, though not statististically significant (p≥0.15). Platelet activation evaluated by sP-selectin was significantly higher in patients with MEA reactivity levels in the upper tertile than in the lower tertile (p=0.0001). Optimal compliance was confirmed by low serum thromboxane B2 levels in all patients. In conclusion, increased levels of hs-CRP were associated with augmented platelet reactivity in stable high-risk CAD patients receiving aspirin as mono antiplatelet therapy. These findings may suggest that chronic low-grade inflammation reduce the antiplatelet effect of aspirin.
Keywords: Aspirin; C-reactive protein; coronary artery disease; inflammation; platelet reactivity